Ni and Ti silicide oxidation for CMOS applications investigated by XRD, XPS and FPP. (15th November 2017) - Rahman, M.K.; Nemouchi, F.; Chevolleau, T.; Gergaud, P.; Yckache, K.
Abstract: Although silicide oxidation was studied 20 years ago, the interest of obtaining a robust process for new application appears significant today. Indeed, for the new architectural development process are required dense and narrow spaces. This paper focuses to bury a silicide layer under a protective layer such as silica in order to keep constant the physical and electrical properties of silicide after oxidation. Earlier works show the possibility to oxidize preferably the silicon (Si) in metal contained silicide rather than a pure crystalline Si at high temperatures. Thus, we first tried to reproduce and study these conditions and once acquired, targeted to decrease the oxidation temperature in order to fit with industrial requirements. Titanium (Ti) and Nickel (Ni) are chosen for their metallurgical interest and their integration capability in devices. Thus, four different group/phases (TiSi, TiSi2, Ni2 Si, NiSi) of silicide were targeted by adjusting the temperature. In situ X-ray diffraction (XRD), photoelectron spectroscopy and sheet resistance (four point probe) measurements were carried out simultaneously before and after oxidation of silicide to characterize the phase and chemical composition. After silicide formation last three phases (TiSi2, Ni2 Si, NiSi) were confirmed by XRD and G1(Ti/Si) was unknown, where only for NiSi was observed the low sheet resistance (≈7.3 Ω/□) and resistivity (18 μΩ·cm). After (dry, wet and plasma) oxidation, the phases of TiSi2 and Ni2 Si changed and only NiSi was observed the constant phase, even pure SiO2 was noted on NiSi after wet oxidation.